First volatile inventory for Gorely volcano, Kamchatka - Aiuppa, A.; Giudice, G.; Liuzzo, M.; Tamburello, G.; Allard, P.; Calabrese, S.; Chaplygin, I.; Mcgonigle, A. J. S.; Taran, Y. (Geophysical Research Letters, 2012)
International audience We report here the very first assessment of volatile flux emissions from Gorely, an actively degassing volcano in Kamchatka. Using a variety of in situ and remote sensing techniques, we determined the bulk plume concentrations of major volatiles (H 2 O ∼93.5%, CO 2 , ∼2.6%, SO 2 ∼2.2%, HCl 1.1%, HF 0.3%, H 2 0.2%) and trace-halogens (Br, I), therefore estimating a total gas release of ∼11,000 tons·day -1 during September 2011, at which time the target was non-eruptively degassing at ∼900°C. Gorely is a typical arc emitter, contributing 0.3% and 1.6% of the total global fluxes from arc volcanism for CO 2 and HCl, respectively. We show that Gorely's volcanic gas (H 2 O/SO 2 ∼43, CO 2 /SO 2 ∼1.2, HCl/SO 2 ∼0.5) is a representative mean end-member for arc magmatism in the north-west Pacific region. On this basis we derive new constraints for the abundances and origins of volatiles in the subduction-modified mantle source which feeds magmatism in Kamchatka.